On the Importance of Heritage Intermediaries in Kosovo and Metohija - Pavličić Šarić, Jelena Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper presents the specific efforts of individuals who contributed to the preservation and affirmation of the monumental heritage of Kosovo and Metohija and evaluates the effects of their engagement. Interpreting the actions of trustees of the protection service, guardians and curators of monuments in Kosovo and Metohija after the Second World War, and immediately after the formation of the service for the protection of cultural monuments, as well as those who followed their work, it was shown what the role of the individual is in the systemic protection of heritage and beyond. The activities of people from different professions who were united by the same commitment—heritage care—are highlighted. The network of trustees was established in the period from 1948 to 1951. These were primarily teachers, but also priests and other educated and respectable people. Their task was to identify and record the cultural heritage in their area, to recognize the risks to the survival of some places and to report this to the Republic Institute for the Protection of Cultural Monuments. Personalities such as Krsta Zivgarević, Nedeljko Virijević, Srećko Lazić and others excelled at this task. They greatly influenced the formation of the Central Register of Monuments. Around the middle of the last century, records of monuments and visitors were kept by the guardians of cultural and historical monuments that were assigned to the most important monuments in Kosovo and Metohija—the church of the Holy Virgin of Ljeviška, the monasteries of Dečani, Peć Patriarchate and Gračanica, as well as Muratovo and Barjaktarevo tulbe. Education was organized for the job of guardians, but their duties approached close to those of heritage interpreters, so soon, in 1957, the curators of the mentioned cultural and historical monuments were also hired. They operated until the 90s of the last century, and their mission was continued in some cases by a devoted individual. We recognized one such person who operated in the city of Prizren. We have recognized the involvement of the community, and especially of dedicated individuals, as part of the social protection of heritage, which in recent decades has been encouraged by international conventions and heritage conservation projects. This work recognizes the importance of the individualization of inheritance, especially in the territory where the operation of the domestic protection service is difficult in the modern times.